Acute coronary syndromes without persistent ST-segment elevation: advances in surgical revascularization - Zoffoli, G.; Nicolini, F.; Beghi, et al., C (Acta Biomedica Atenei Parmensis, 2005)
Coronary artery bypass grafting (CABG) still plays a fundamental role in the management of acute coronary syndromes. The aim of this study is to report the experience of our center in the treatment of patients with acute coronary sindromes without persistent ST elevation urgently operated on with CABG, and to discuss surgical problems related.Two-hundred and six patients were urgently operated on for CABG for acute coronary syndromes without persistent ST-segment elevation from January 2001 to February 2003. The majority of them had three vessel coronary disease (72%) and left main stem disease occurred in 20% of the patients. Mean LVEF (left ventricular ejection fraction) was 54±12% whereas 9% of the patients had a LVEF